A Five-Year strategic financial plan for Ginebra San Miguel, Inc. - Miguel Edward V. De Jesus, Alexandra S. Dela Cruz, Cherry Mae R. Fernandez, Kyla C. Ferrer, Ritchell C. Mandaloda, Kyla F. Raguimia, Andrea M. Yanga 4 0 16; 5
Executive Summary: This paper provides an analysis of Ginebra San Miguel's performance over the past five years, utilizing financial statements from 2019 to 2023. By utilizing a range of financial ratios, we assessed key aspects of the company's financial health, including its liquidity, profitability, and solvency. The analysis also provides insights into how Ginebra San Miguel has navigated market challenges, managed its resources, and maintained its competitive position. With this, it provides a clearer understanding of the company's overall financial well-being and identifies trends that may inform future strategies. In our assessment, we carefully examined the financial status of Ginebra San Miguel and found that it is performing well. With this in mind, we transformed our challenge into an opportunity. We propose a strategy to expand GSMI's market reach into the Southeast Asia region. Given its established brand and high-quality products, GSMI has significant potential to tap into new markets within this region. The expansion strategy would involve identifying high-growth areas in Southeast Asia, tailoring marketing efforts to align with local tastes and preferences and establishing strategic partnerships with local distributors and retailers to ensure a smooth market entry and long-term success. By diversifying its geographic footprint, GSMI can mitigate risks associated with domestic market saturation and take advantage of the robust growth opportunities available in Southeast Asia. The group also discussed various alternative actions the company could take to address its opportunities. One potential approach is to increase and stabilize both gross profit and net profit margins. The company plans to expand into non-alcoholic beverages, such as wellness drinks and juices, targeting health-conscious and younger consumers. Additionally, GSMI will introduce premium alcoholic and non-alcoholic products to cater to middle-class and affluent markets, enhancing profitability through high-value offerings. Another key action is to achieve cost-effective and environmentally friendly operations. GSMI plans to adopt renewable energy sources, such as solar and wind power, to reduce reliance on volatile fossil fuel markets and lower operational costs. The company will also implement sustainable practices, including the use of recycled PET (rPET) in packaging, developing lightweight bottles to reduce material usage and transportation costs, and enhancing the recyclability of its packaging. These initiatives will not only minimize environmental impact but also strengthen GSMI's reputation as a socially responsible and forward-thinking company, resonating with eco-conscious consumers and stakeholders Ginebra San Miguel, founded in 1834, is the Philippines' oldest gin brand and a cultural emblem of Filipino traditions. Renowned for its flagship product, Ginebra San Miguel Gin, which features St. Michael the Archangel on its label, it proudly holds the title of the world's best-selling gin, with millions of cases sold annually. As a subsidiary of San Miguel Corporation, the brand has embraced innovation, introducing flavoured gins and ready-to-drink options to meet diverse consumer preferences. Ginebra San Miguel has earned numerous international awards for its quality and has made significant contributions to the Philippine economy by creating jobs and supporting local industries. Additionally, the brand is dedicated to corporate social responsibility and is actively involved in sports, notably as a sponsor of the Barangay Ginebra San Miguel team in the Philippine Basketball Association (PBA). Its enduring legacy and commitment to innovation reinforce its position as a vital part of Filipino heritage and a leader in the global spirits industry.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2